Skin effect of chloride ingress in marine concrete: A review on the convection zone - Cai, Rong; Hu, Yingshuang; Yu, Miao; Liao, Wenyu; Yang, Lufeng; Kumar, Aditya; Ma, Hongyan (Construction & building materials, 2020)
•Characteristics of convection zone depend on environmental classes, mix proportion, exposure time, etc.•Convection zone in submerged zone may not be ignored.•Convection zone in the atmospheric zone has the largest variance and can be as thick as that in tidal and splash zones.•Reducing water-to-binder ratio appears to be the most effective method to weaken the skin effect. The formation mechanism on the convection zone (“skin effect”) of chloride ingress are explored systematically by contrasting concretes in marine atmospheric, splash, tidal, and submerged zones. The depth of convection zone, Δx, and the maximum chloride concentration, Cmax, are two important indicators for estimating the degree of action of the skin effect. Influences of various factors on the skin effect are analyzed, including environmental conditions, mixture proportion, exposure time, and construction method. Statistics of the Δx and Cmax were extracted from field test data in the literatures. Influence of skin effect on the apparent surface chloride concentration (Cs) and diffusion coefficient (Da) was analyzed. Results show that the skin effects of concrete in atmospheric, tidal, splash and submerged zones are different, and it is highlighted that the convection zone exists even in submerged zone. The skin effect of concrete significantly impacts the fitting values of Cs and Da. Effective processing approaches can account for the skin effects of the concrete during durability design.